Metaphysics, Reductivism, and Spiritual Discourse - Carr, David McLain (Zygon, 2002)
Although significant revival of talk of the spiritual and spirituality has been a striking feature of recent public debate about wider social and moral values in contemporary Western liberal-democratic polities, it seems worth asking whether there might be any substantial philosophical basis for such renewal. On the face of it, any meaningful discourse about spirituality seems caught between the rock of an antiquated mind-body dualism—now widely regarded (some notable contemporary pockets of resistance aside) as implausible—and the hard place of a scientific physicalism that offers little harbor for irreducible spiritual entities. The present essay explores two possibilities of escape from this dilemma in the shape of eliminative dualism and noneliminative monism and argues for the conceptual advantages of the second over the first of these possibilities.